Design and implementation of ultra high frequency 921 MHz reader antenna for indoor propagation / Syamimi Mohd Norzeli - Mohd Norzeli, Syamimi (2017)
In recent years, Radio Frequency Identification (RFID) technology is highly demanded in various applications, requiring a rapid development in the RFID technology. The Ultra High Frequency (UHF) RFID reader was selected for this research due to its further detection distance compared to the High Frequency (HF) and Low Frequency (LF). The research described in this thesis focuses on the development of the UHF RFID reader microstrip antenna designs to meet the requirements of certain applications which are long read range detection and in a small area. The proposed reader antenna has a unique and innovative design as it uses a combination of circular polarized technique, array, parasitic elements and complementary split ring resonator (CSRR) in order to increase gain and miniaturized the reader antenna.